Analysis of Suspended Marriages from The Perspective of Human Rights and Child Protection Laws - Zinqi, Navila; Fakhruddin Aziz (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
Early marriage by minors becomes a problem in many countries including Indonesia, with economical, educational and customary factors being the main reasons. In some areas in Indonesia where customs are still closely held, the practice of suspended marriages is very common. Suspended marriage is a condition where marriage is carried out when each partner is very young with a specific purpose and both are prohibited from living together in the same house before adulthood. This article aims to examine suspended marriage in human rights’ perspective and child protection law’s using normative research techniques by reviewing and deepening literature studies. The results of this study indicate that suspended marriages are included in the marriage of minors which is an act categorized as violating human rights because child marriage affects the education and growth of children and is a form of opposition to the Child Protection Law, the practice of early marriage and suspended marriages often occur in Indonesia even though the law has expressly prohibited doing so.